Epidemiological, clinical and histological profile of oral carcinomas at the Sylvanus Olympio University Hospital in Lome - Agoda, Palakina P.; Bouassalo, Komlan M.; Amana, Essobiziou; Foma, Winga; Pekoula, Gbandi; Amana, Bathokedeou; Darré, Tchin (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Background: Early detection of oral carcinomas is a crucial public health issue. The aim of this study was to describe the epidemiological, clinical and histopathological profile of carcinomas diagnosed in a referral healthcare facility in Lomé Methods: A retrospective descriptive study was conducted over a period of 10 years, including the medical records of patients presenting with carcinoma of the oral cavity confirmed by anatomopathological examination. Clinical and histopathological socio-demographic parameters were collected and analysed using R software version 4.0.4. Results: Forty-five (45) cases of carcinoma of the oral cavity were included, with an annual frequency of 4.5 cases. Males predominated with 68.9% of cases. The age group 55 and over was the most affected, with 71.2% of the sample. Alcohol was the most common risk factor (82.2%). The tongue was the preferred site of oral carcinomas with 55.5% and squamous cell carcinoma was the most common histological type. Conclusions: The carcinoma of the oral cavity in Lomé are predominantly male, in relatively elderly patients with an alcohol-smoking past. While awaiting more in-depth studies on risk factors, raising awareness of the harmful effects of these factors will make it possible to deduce the incidence and morbidity of carcinomas in Togo.